Ziarah Ramadhan to new converts muslim village: Kampung Semalatong - Dim, AJ (Universiti Teknologi MARA, Sarawak, 2006)
The trip to Kampung Semalatong, Simunjan on 28 October 2005 was organized jointly by the KEKITA Club and HIKMAH Samarahan and Simunjan. Kampung Semalatong is a new Muslim village where the villagers are new Iban-Muslim converts. According to the organizer, En. Khalid Ibrahim, the objective of this visit was to foster closer fraternity among the villagers. We departed from UiTM Samarahan at 3.30 pm with approximately 36 participants. Among the passengers were the UiTM staff, HIKMAH Samarahan representatives, Student Council representatives (MPP), students and also villagers from Samarahan. We were later joined by our Assistant Director, Prof. Madya Dr. Abang Ahmad Ridzuan Abang Awit who is the Chairman of HIKMAH Samarahan. The journey took about 2 hours and when we arrived, we were warmly received by the Kampung Semalatong villagers. As soon as we arrived, we performed Asar prayer with the villagers. Next, we took a walk around the Kampung while waiting for the breaking of fast and the Maghrib prayer.